Cloning and characterization of a mammalian pseudouridine synthase. - Chen, J (1999)
This report describes the cloning and characterization of a pseudouridine (psi) synthase from mouse that we have named mouse pseudouridine synthase 1 (mpus1p). The cDNA is approximately 1.5 kb and when used as a probe on a Northern blot of mouse RNA from tissues and cultured cells, several bands were detected. The open reading frame is 393 amino acids and has 35% identity over its length with yeast psi synthase 1 (pus1p). The recombinant protein was expressed in Escherichia coli and the purified protein converted specific uridines to psi in a number of tRNA substrates. The positions modified in stoichiometric amounts in vitro were 27/28 in the anticodon stem and also positions 34 and 36 in the anticodon of an intron containing tRNA. A human cDNA was also cloned and the smaller open reading frame (348 amino acids) was 92% identical over its length with mpus1p but is shorter by 45 amino acids at the amino terminus. The expressed recombinant human protein has no activity on any of the tRNA substrates, most probably the result of the truncated open reading frame.